The 2nd International Cell Death Research Congress 2018
DOI: 10.3390/proceedings2251587
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Inhibits PI3K/AKT/mTOR Signaling Pathway in Mice Kidneys

Abstract: Cyclophosphamide (CTX), also known as cytophosphane among other, is a medication used as chemotherapy and to suppress the immune system. The PI3K/AKT/mTOR pathway is involved in the regulation of diverse cellular functions, including cell growth, protein synthesis, cell cycle regulation, glucose metabolism, and motility. In our study eight weeks old C57BL/6 female mice were divided into 3 groups as control (C), sham (S) and experimental group. The experimental group has been established with CTX treatment. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Multiple vacuolations (V) can be observed FoxO1. In accordance with our results, the study of Albayrak et al reported the repression of PI3K, Akt expression in the renal tissues of mice cured with CP (Albayrak et al 2018). Moreover, earlier studies have clarified the repressive effect of the anticancer medications on the PI3K/Akt axis mediating oxidative stress occurring with these drugs (Zhu et al 2009;Sun et al 2014a, b).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple vacuolations (V) can be observed FoxO1. In accordance with our results, the study of Albayrak et al reported the repression of PI3K, Akt expression in the renal tissues of mice cured with CP (Albayrak et al 2018). Moreover, earlier studies have clarified the repressive effect of the anticancer medications on the PI3K/Akt axis mediating oxidative stress occurring with these drugs (Zhu et al 2009;Sun et al 2014a, b).…”
Section: Discussionsupporting
confidence: 91%
“… 63 , 64 The current study showed the downregulation of PI3K, Akt and mTOR expression in the heart of rats administered with CP. In accordance, the study of Albayrak et al 65 demonstrated the downregulation of PI3K, Akt and mTOR expression in the kidney of mice received CP every 2 days for 3 consecutive weeks. Given the role of the PI3K/AKT/mTOR pathway in maintenance of the cardiac structure and function and its suppression by CP, it would be intriguing to know whether the modulation of this pathway is involved in the cardioprotective effects of AV and ED.…”
Section: Discussionsupporting
confidence: 71%
“…This notion is supported by the studies showing the inhibitory effect of the anticancer drug doxorubicin on the PI3K/Akt/mTOR pathway in cardiomyocytes (Lee et al, 2015; Zhu et al, 2009). In addition, PI3K, Akt, and mTOR expression was downregulated in the kidney of mice received CP for three consecutive weeks (Albayrak, Sonmez, Akogullari, & Uluer, 2018). Oral supplementation of AV upregulated PI3K, Akt, and mTOR in the lung of CP‐intoxicated rats, pointing to the involvement of PI3K/Akt/mTOR signaling in the protective effect of AV against CP‐induced AKI.…”
Section: Discussionmentioning
confidence: 99%